A mis-splicing early flowering 3 (elf3) allele of lentil is associated with yield enhancement under terminal heat stress - Roy, Anirban; Reddy, M. Hemakumar; Sarkar, Moutushi; Sagolsem, Diana; Murmu, Sumit K.; Das, Camellia; Roy, Debarati; Ganguly, Shamba; Nath, Rajib; Bhattacharyya, Prabir K.; Sarker, Ashutosh; Bhattacharyya, Somnath (Springer, 2023)
There is a vast scope of area expansion of lentils after harvesting wet rice in South Asia. However, due to the photoperiod effect and terminal heat, the existing short-duration varieties failed to minimize yield loss under late-sown conditions. A mis-splicing causing A/G SNP present in the last nucleotide of exon 3 of early flowering 3 (ELF3) gene (elf3 allele) in a lentil line, L4710, is associated with the photoperiod insensitive flowering and the fast absolute growth rate (AGR). None of the Indian cultivars tested in this study, either early or late, possesses the non-functional elf3 allele. However, the A to G transition in ELF3-exon2 replaces glycine with aspartic acid at the 403rd amino acid in all the Indian varieties tested, compared to the reference sequence of Mediterranean accession, ILL5588. Therefore, targeting A/G SNP of exon 3, a PCR-based codominant marker is developed. The elf3 allele is correlated with the fast AGR and early flowering, but low yield and biomass, in an L4710 × LL56–derived RIL-population, compared to ELF3 carrying alleles when sown on 15th November. However, in a month of delayed sowing (20th December), the same elf3-RILs revealed a higher yield and biomass with slower AGR Moreover, three elf3-carrying lines, grown in delayed condition (20 December) for two consecutive years in three locations, outyielded three popular high-yielding cultivars that carry functional ELF3. Thus, elf3-carrying high-yielding lines could be the breeder’s choice to expand and enhance lentil yield in short-season environments and in vast rice fallows of south Asia, where delayed rice harvest occurs frequently.